Comparative analysis of punching and blocking techniques in boxing across eight weight divisions - Mohd Zamri, Muhamad Akasyah; Yusof, Aliah Sahira; Mohamed, Muhamad Noor; Saiful Annur, Muhamad Safiq; Adnan, Mohd Aizzat; Mazaulan, Mardiana; Md Radzi, Noor Azila Azreen (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates how boxing techniques—including jabs, hooks, uppercuts, and defensive blocks—vary across different weight classes to influence match outcomes and strategic adaptation. By bridging the gap between biomechanical dynamics and weight-specific performance, the research explores how body size dictates the deployment of punches that produce varying levels of joint acceleration. The findings aim to clarify the relationship between mechanical complexity and weight division, providing coaches and athletes with insights into the technical execution and defensive strategies unique to different competitive tiers.